Changes on structural and electrical properties of retired cross-linked polyethylene (XLPE) cable insulation under electro-thermal aging test. (October 2019) - Huang, J S; Lu, R G; Shi, Y X; Zhao, Y F; Huang, J X; Fang, X H; Liu, G; Li, Z J
Abstract: In order to study the insulation performance of two retired high voltage cross-linked polyethylene (XLPE) cables with service years of 16 and 32 and evaluate the reliability of reusing these cables for actual operation, a 180-day electro-thermal aging test was exerted on a section of these two cables to inspect the changes on structural and electrical properties. Several diagnostic measurements including fourier infrared spectroscopy (FTIR), differential scanning calorimetry (DSC) and breakdown field strength were carried out on the untreated and treated samples. The measured results show that the crystalline structure of the 16 years cable has been improved after the accelerated aging test probably because of the reduction of the impurities and the annealing effect, which further improve the electrical property. Even though the molecular chains of the 32 years cable insulation has been damaged and a slight degradation happens on the crystalline structure under the intensive aging test condition, which is responsible for the decline in the electrical property, the cable still have the potential to resist the stresses properly under the actual operation condition for a long time from the perspective of the XLPE. Therefore, it can be expected that the rest of these two retired cables still have the ability to reuse in the long-term actual operation condition.